Phylotranscriptomics supports numerous polyploidization events and phylogenetic relationships in Nicotiana - Wang, Shuaibin; Gao, Junping; Li, Zhaowu; Chen, Kai; Pu, Wenxuan; Feng, Chen (Frontiers in Plant Science, 2023)
Nicotiana L. (Solanaceae) is of great scientific and economic importance, and polyploidization has been pivotal in shaping this genus. Despite many previous studies on the Nicotiana phylogenetic relationship and hybridization, evidence from whole genome data are still lacking. In this study, we obtained 995 low-copy genes and plastid transcript fragments from the transcriptome datasets of 26 Nicotiana species, including all sections. We reconstructed the phylogenetic relationship and phylogenetic network of diploid species. The incongruence among gene trees showed that the formation of N. sylvestris involved incomplete lineage sorting. The nuclear–plastid discordance and nuclear introgression absence indicated that organelle capture from section Trigonophyllae was involved in forming section Petunioides. Furthermore, we analyzed the evolutionary origin of polyploid species and dated the time of hybridization events based on the analysis of PhyloNet, sequence similarity search, and phylogeny of subgenome approaches. Our results highly evidenced the hybrid origins of five polyploid sections, including sections Nicotiana, Repandae, Rusticae, Polydicliae, and Suaveolentes. Notably, we provide novel insights into the hybridization event of section Polydicliae and Suaveolentes. The section Polydicliae formed from a single hybridization event between maternal progenitor N. attenuata and paternal progenitor N. undulata; the N. sylvestris (paternal progenitor) and the N. glauca (maternal progenitor) were involved in the formation of section Suaveolentes. This study represents the first exploration of Nicotiana polyploidization events and phylogenetic relationships using the high-throughput RNA-seq approach. It will provide guidance for further studies in molecular systematics, population genetics, and ecological adaption studies in Nicotiana and other related species.